Modality Acts as a Strategic Pedagogical Support: Exploring Face, Stance, and Participation In EFL Learners’ Classroom Interactions - Syam, Nur Ina; Ramadhani, Ahmad Arkam; Thamrin, Sri Wahyuni; Room, Fahmi; Ulfa, Andi Yurni; Chapakiya, Suraiya (JOLLT Journal of Languages and Language Teaching, 2026)
The importance of understanding modality role as pedagogical support in helping EFL learners manage face, build stance, and regulate participation in higher education contexts. This study aims to explore how modalities function as pedagogical support in helping English as a Foreign Language (EFL) learners manage face, negotiate stance, and regulate participation in a higher education learning context. Using a qualitative phenomenological approach, data were collected through in-depth interviews with 13 fifth-semester students of the English Language Education Study Program at Muhammadiyah University of Bulukumba. The research findings indicate that modalities—presented through text messages, voice recordings, emojis, gestures, intonation, and digital communication features—play a significant role in reducing anxiety, increasing self-confidence, and providing more flexible access to participation for students. Participants viewed modalities as “safe communication spaces” that allowed EFL students to express ideas, refine language structures before use, and negotiate meaning without direct pressure. To support language production, modalities also shape learners’ identities, social positioning, and emotional engagement in academic interactions. This study concludes that modality acts as a strategic pedagogical support that helps EFL learners manage their identity, attitudes, and participation more confidently and adaptively in academic interactions. The implication is that lecturers need to consciously integrate multimodal strategies into learning design to support face management, stance strengthening, and increasing students’ participation. This study contributes the language pedagogy and sociolinguistics by asserting that modality functions as an interactional resource that mediates face management, stance formation, and participation structures in EF contexts.